Assessment of soil quality in hanzhong city based on risk management of heavy metal pollution - Wang, Tao (Bangladesh Journal of Botany, 2023)
In the present study, Hanzhong City was taken as an example, and the classification of soil heavy metal pollution risks was performed based on the evaluation of soil fertility status with soil physical and chemical properties as the main indicators. Results showed that the coefficients of variation of soil physical and chemical indicators in the study area were in the descending order: the soil fertility status showed a trend of increasing with decreasing terrain and increasing rivers. The high fertility areas were mainly distributed in the northwest and northeast of the plain area, while the low fertility areas were mainly distributed in the southeastern hilly and mountainous areas and in the western low-lying areas, and the transitional areas surrounded the low-fertility areas. At least 88.89% of the Cd samples and 98.61% of the Cr samples out of the eight heavy metals, Cd, Hg, As, Pb, Cr, Ni, Cu, and Zn, belonged to the priority protection class, while 11.11% of the Cd samples and 1.39% of the Cr samples belonged to the safe use class. The overall distribution of soil quality was similar to that of soil fertility status, while the distribution range of low-quality soil in the southeastern part was smaller and more concentrated. The above research results indicate that the introduction of the classification results of soil pollution risk control types generally reduces the soil fertility status correction and changes the spatial distribution pattern of the original soil fertility status to some extent. Bangladesh J. Bot. 52(2): 659-669, 2023 (June) Special